Sequência didática e o interacionismo sociodiscursivo na geografia escolar: propostas teórico-metdologógicas - Silva, Wellington Domingos Pereira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work has as main objective to discuss the contribution that the instructional sequence and production of written text genres have on the Geography teaching and learning process of students from the ninth grades of elementary school. For this, we rely on the principles of sociodiscursiveinteracionism by Jean Paul Bronckart, as well as the conceptions of Teaching Sequence and genres by Joaquim Dolz and Bernard Schneuwly, the perspective of discussions on discursive genres by Mikhail Bakhtin. Therefore, we constructed a didactic sequence on the subject Globalization and consumerism and apply this standard in the first quarter of 2014. In the analysis, we seek to observe the results in the teaching learning process, once the activities during the Didactic Sequence allow to see the advances in the fields of language and content. These results show that each student, one way or another, in their written textual productions managed to trace a dialogue with intertexts presented during our intervention. We also note that, prior to implementing the modules of the Sequence, when there was the initial production, the discussion of the students were quite superficial or equivocal about the phenomena depicted. However, in advancing the modules, we realized the incorporation of stronger arguments in the speeches of these students. Another relevant aspect is the creative potential, which despite some difficulties with gender, or with the subject, brought to their textual productions discussions with extremely sharp criticism associated to comical. We noted, finally, that advances with the activities in the light of sequence and genres, were very significant. For the students, there was a greater changeability in their learning (both specific content of Geography, as the mechanisms of language); for the teacher, a new way of thinking and intervene in the teaching learning process within the classroom, breaking with traditional and inefficient due ...

Este trabalho tem por objetivo central discutir a contribuição que a Sequência Didática e a produção de Gêneros Textuais escritos têm no processo de ensino aprendizagem de Geografia de alunos do nono ano do Ensino Fundamental. Para isso, nos apoiamos nos princípios do Interacionismo Sociodiscursivo de Jean- Paul Bronckart, bem como nas concepções de Sequência Didática e Gêneros Textuais de Joaquim Dolz e Bernard Schneuwly, sob a ótica das discussões sobre gêneros discursivo de Mikhail Bakhtin. Diante disso, construímos uma Sequência Didática sobre o tema Globalização e consumismo, com aplicação de atividades no primeiro trimestre de 2014. Nas análises, buscamos observar os resultados no processo de ensino aprendizagem, uma vez que as atividades desenvolvidas ao longo da Sequência Didática permitem visualizar os avanços nos campos da linguagem e do conteúdo. Estes resultados mostram que cada aluno, de uma maneira ou de outra, em suas produções textuais escritas conseguiu traçar um diálogo com os intertextos apresentados ao longo de nossa intervenção. Observamos também que, antes da aplicação dos módulos da Sequência, quando houve a produção inicial, as discussões dos alunos foram bastante superficiais, quando não equivocadas sobre os fenômenos retratados. No entanto, ao avançar dos módulos, já percebíamos as incorporações de argumentações mais sólidas nas falas destes alunos. Outro aspecto relevante reside no potencial criativo que, mesmo diante de algumas dificuldades com o gênero, ou com o tema, trouxe para suas produções textuais discussões que apresentaram críticas bastante aguçadas. Por fim, identificamos que os avanços com as atividades, à luz da Sequência e dos Gêneros, foram muito significativos, uma vez que, por parte dos alunos, houve maior transformação em sua aprendizagem (tanto de conteúdos específicos de Geografia, quanto dos mecanismos da linguagem); para...
Keywords: Geography - Study and teaching; Geografia - Estuso e ensino; Ensino fundamental; Globalização; Sociedade de consumo